2011
DOI: 10.1111/j.1751-1097.2011.00968.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐level Laser Therapy Improves Skeletal Muscle Performance, Decreases Skeletal Muscle Damage and Modulates mRNA Expression of COX‐1 and COX‐2 in a Dose‐dependent Manner

Abstract: We tested if modulation in mRNA expression of cyclooxygenase isoforms (COX-1 and COX-2) can be related to protective effects of phototherapy in skeletal muscle. Thirty male Wistar rats were divided into five groups receiving either one of four laser doses (0.1, 0.3, 1.0 and 3.0 J) or a no-treatment control group. Laser irradiation (904 nm, 15 mW average power) was performed immediately before the first contraction for treated groups. Electrical stimulation was used to induce six tetanic tibial anterior muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 31 publications
4
42
0
4
Order By: Relevance
“…Previous studies have used light therapy for muscular preconditioning by delivering the light therapy over the target muscles 5 min before fatigue tests in vivo [27,28] or in clinical trials [20][21][22]. These studies reported an increased number of repetitions and consequently a better fatigue-muscle resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used light therapy for muscular preconditioning by delivering the light therapy over the target muscles 5 min before fatigue tests in vivo [27,28] or in clinical trials [20][21][22]. These studies reported an increased number of repetitions and consequently a better fatigue-muscle resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of low-level laser (light) therapy on muscle tissue when applied before or after intense exercise are mainly related to the prevention of exercise-induced damage, promotion of faster muscle recovery, and also producing increases in performance [10,30,11]. The use of LLLT to prevent muscle damage has been widely investigated in experimental models [15][16][17][18][19][20] and in clinical trials [21][22][23][24][25][26][27][28]. Experimental studies have used animal models to induce muscle damage, and clinical trials have used protocols of exercise in isokinetic dynamometers, fitness machines, or free weight lifting to induce muscle damage.…”
Section: Discussionmentioning
confidence: 99%
“…More studies using experimental models were conducted to investigate the effects of LLLT on CK activity [18,17,19,20]. Using a similar model of neuromuscular electrical stimulation previously reported [15], other studies also found LLLT dose responses of muscular pre-conditioning by decreased CK activity [18,19], including assessment of different wavelengths [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the analgesic effect of LLLT is thought to be related to its antiinflammatory action (12)(13)(14)(15). Many experimental and clinical studies have shown that LLLT can reduce or modulate TNF-α levels (13,15).…”
Section: Introductionmentioning
confidence: 99%